Mobile and web application development for monitoring patients - Koh, ZhiQuan. (2011)
Mobile devices’ capabilities have improved exponentially over the years and are inseparable from our daily lives. The integration of Smartphones technologies with healthcare will provide a seamless approach for improving communications between physicians, care givers and their patients. The development of this project will allow users such as doctors and nurses to remotely monitor and be alerted of their patients’ vital signs such as pulse and respiration anywhere and anytime. The project deliverables includes the Web applications, database and mobile application as well as the integrations of these three systems.